HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI DENGAN KEJADIAN INFEKSI CACING PADA PEKERJA SAMPAH - Wa Ode Sitti Asfiah Udu; Sulastrianah Sulastrianah; Lezdyana Nur Islami (Halu Oleo University, 2014)
The prevalence of helminth infection in developing country is higher than other country according World Health Organization (WHO) in 2006. Incidence of helminth infection more common in childrens, but adult withspecial job like garbage workers have same risk with that childrens. The aim of this study is to determine relation between usage of personal protective equipment with the helminth infection in garbage workers. The method of thisstudy is an observational with cross sectional design. Population in this study are garbage workers at Sanitary Service Wakatobi Regency. Sampling method using total sampling with 59 samples. Data collection using questionnaire and faecal examination. and analysed statistically using Chi-Square test. As a result, it is obtained that among the workers that not fully using personal protective equipment, there 27 (60%) samples are infected and 18 (40%) samples are not infected. Among the workers that fully using personal protective equipment, there is 4 (28,6%) samples are infected and 10 (71,4%) samples are not infected (p = 0,04). The conclusion of this study is there was relation between usage of personal protective equipment with helminth infection in garbage workers. Key Words: Helminth infection, garbage workers, personal protective equipment